(3GdgOGjI TQM GdHOGjIs - (3GdnerQpZjfGfj GdaQZGfj, CHh GdMSf, HQgGf GdOjf, Ydj Hf CHj HcQ Hf YHO GdLdjd, (B593 (3g`s
(3ChdgG (B:s
(3dG ZjQ Ch fhi GdfPQ hfhi Cf dG jchf jejfG jchf fPQG dCfg fPQ HUjZI cja hbO bQQg HYRjeJg hEf fhi Gdjejf hfhi Cf dG jchf fPQGs
(3BNQgG (B:s
(3HGTJQGW GdYed YdjgeG bGd hjLhR Cf jYbOgeG cd hGMO efgeG HHYV eGdg Ohf GdHYV dCf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 266s
(3eYLe GdeDdajf (B2 / 411s
(3cTa GdXfhf (B2 / 2031s
(3gOjI GdYGQajf (B1 / 702s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs